Absorption of Carbon Dioxide into Aqueous Ammonia Solution using Blended Promoters (MEA, MEA+PZ, PZ+ArgK, MEA+ArgK) - Farah Al-Sudani (Engineering and Technology Journal, 2020)
Absorption of CO2 into promoted-NH3 solution utilize a packed column (1.25 m long, 0.05m inside diameter) was examined in the present work. The process performance of four different blended promoters monoethanolamine (MEA)+ piperazine (PZ), piperazine (PZ)+ potassium argininate (ArgK) and monoethanolamine +potassium argininate was compared with unpromoted-NH3 solution by evaluated the absorption rate (φ_(CO_2 )) and overall mass transfer coefficient (K_(G,CO_2.) a_v) over the operating ranges of the studied process variables (1-15Kpa initial partial pressure of CO2, 5-15 Liter/min gas flow rate, 0.25-0.85 Liter/min liquid flow rate). The results exhibit that the absorption behavior and efficiency can be enhanced by rising volumetric liquid flow rate and initial CO2 partial pressure. However, the gas flow rate should be kept at a suitable value on the controlling gas film. Furthermore, it has been observed that the (PZ+ArgK) promoter was the major species that can accelerate the absorption rate and reached almost 66.166% up to123.23% over that of the unpromoted-NH3 solution.